REVOLUSI HIJAU DAN GERAKAN PETANI DI MAGELANG PADA MASA AKHIR ORDE BARU - , Nor Huda, S.Ag; , Prof. H. Djoko Suryo, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examines the movement by peasants against the Green Revolution. Here, organic agriculture is used as an ideological movement, which in it contains the values of freedom, independence and balance of nature. The research focus of this thesis is why these movements emerged, how this movement lasted, and what its impact. In answer to some of these problems required the reconstruction of events with a critical historical method. Sources of writing are derived from primary and secondary data. The first was obtained by tracking the archive, in-depth interviews and direct observation, while the secondary data derived from several studies of the relevant literature. The results of this study are as follows. Independence of farmers was initiated with the ideology of organic farming is not going according to expectations. In political economy, the organic farming movement can be said to fail. The obstacles are no longer lies in government policy, but the mentality of the farmers themselves who have turned into a rational farmer, in the sense of a modern farmer. Organic farming is more grounded in moral ideal simply fail to thrive because of the conditions of land ownership, the difficulty of supporting facilities, and the condition of the land itself. Therefore, the issue of organic farming is segmented into three groups: the moralists, idealists (theological-philosophical), rational-economic, and technical-pragmatic. In such cases, Suko who lived in the hamlet Kenteng, Mangunsari, Sawangan is symbolized as a figure of resistance movement by peasants. The creation of the impression was deliberately created by NGOs for political purposes. The media plays an important role in construction the imaging is a way to redirect a frame of interpretation of public opinion. Then, the opinion that had has developed reproduced by other mass media. The result, Suko managed to become a celebrity figure in the resistance movement of peasants in the last New Order era.